How Unplanned Changes Emerge while Implementing a Project Management Information System (PMIS) in a Complex Multi Project R&D Environment. (2nd July 2015) - Tromp, Jan Willem; Homan, Thijs
Abstract: While implementing our Project Management Information Systems (PMIS) I experienced that despite an approved implementation plan small local interactions can create huge unplanned changes. In my role as an implementing consultant I am part of the politics, loyalty, anxiety, power and conflict that influence the implementation process. In order to get better understanding of what happens and how this influences the implementation and my personal role, I used a reflective narrative approach as research as a practice (auto-ethnographic). After the reflection I studied beside literature from the dominant discourse also an alternative view called the complex responsive processes view of relating. The main conclusion is that the complex responsive processes view gives extra insight in what is actually happening. It helped me to invalidate my assumptions about implementation. In that respect both views are complementary and deserve further research.